Efficacy of parenteral pantoprazole in patients with acute ulcerative gastroduodenal bleeding at high risk of relapse - S. G. Shapovalyants; S. A. Chernyakevich; A. I. Mikhalev; O. I. Yudin; I. V. Babkova; G. N. Storozhuk; Ye. K. Mayat; P. L. Chernyakevich (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To determine efficacy of complex treatment of patients with acute ulcerative gastroduodenal bleeding (AUGDB) with high risk of relapse including endoscopic hemostasis, basic intensive antisecretory treatment by «Sunpraz» (pantoprazole) in combination to antihelicobacter agents.Material and methods. Overall 30 patients with AUGDB, including 17 cases of stomach ulcer, 13 cases of duodenal ulcer were investigated. Acute symptomatic ulcers were diagnosed in 14 patients, peptic ulcer – at the other 16. In 17 cases ulcerative bleeding developed on a background of severe concomitant cardio-vascular disease. Of them 19 were men, 11 – women, mean age 53 and 73 years respectively, 81,8 % of patients over 65 years old. Esophagogastroduodenoscopy data (EGDS) indicating the source of bleeding, its intensity (according to Forrest classification), risk of relapse were analyzed. Injection method, argon plasma laser coagulation, clipping of the vessel were applied for endoscopic hemostasis. Bolus intravenous injection of 40 mg of sunpraz, followed by infusion of 160 mg of sunpraz by infusion for 3 days at intensive care unit was carried out. EGDS was repeated on the 2, 4, 7 and 14th day for evaluation of treatment efficacy.Results. At admission ongoing AUGDB (Forrest Iа) was revealed at 6 patients, bleeding from under a clot (Forrest Iв) – in 2 patients, bleeding stopped at the time of examination (Forrest IIа) – in 14, with fixed thrombus (Forrest IIв) – in 8. Endoscopic hemostasis in combination to intravenous sunpraz injection in the majority of patients resulted in arrest of bleeding. Relapse developed only in 2 person. Five patients died of concomitant diseases.Conclusions. Injection of sunpraz with subsequent oral intake of the drug in combination to endoscopic hemostasis and antihelicobacter treatment is an effictive method of treatment of AUGDB at high risk of relapses.